PENGARUH MEDIA SOSIAL DAN REVIEW PRODUK TERHADAP MINAT BELI PRODUK SCARLET DI SHOPEE - Novita, Ririn Septiana; Rossanty, Yossie; Erwansyah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The research analysis aims to determine the influence of social media and reviews on interest in buying Scarlet products on Shopee. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This research uses multiple linear regression analysis. The sample in this study was 120 respondents. Primary data collection uses a questionnaire. The research results show that the social media variable shows a tcount value of 8.450 > ttable of 1.98 with a significant value of 0.000 <0.05, so hypothesis H1 is accepted and H0 is rejected, meaning that social media has a partially positive and significant effect on interest in buying Scarlet products in Shopee. The test results for the review variable show a tcount value of 3.116 > ttable of 1.98 with a significant value of 0.002 <0.05, so hypothesis H2 is accepted and H0 is rejected, meaning that reviews have a partially positive and significant effect on interest in buying Scarlet products at Shopee. Simultaneous test results show that the calculated F value is 200.386 which is greater than 3.07 and the significant value of 0.000 is smaller than 0.05 so it can be concluded that hypothesis 3 is accepted and hypothesis 0 is rejected so it can be concluded that social media and reviews have an influence simultaneously positive and significant on interest in purchasing Scarlet products on Shopee